Associations of Circulating Osteoglycin With Bone Parameters and Metabolic Markers in Patients With Diabetes - Starup-Linde, Jakob Kau; Viggers, Rikke; Langdahl, Bente; Gregersen, Soeren; Lykkeboe, Simon; Handberg, Aase; Vestergaard, Peter (Frontiers in Endocrinology, 2021)
Objective: Circulating osteoglycin may facilitate the crosstalk between bone and pancreas to empower adaptation of bone mass to whole body energy balance. We aimed to examine whether osteoglycin is associated with bone and metabolic parameters and if osteoglycin levels differ between patients with type 1 and 2 diabetes (T1D and T2D). Design and methods: A cross-sectional study of 190 patients with diabetes mellitus and stable hemoglobin A1c (HbA1c) (97 T1D and 93 T2D) was conducted. S-osteoglycin was analyzed by ELISA. Unpaired t-tests were performed to test differences between patients with T1D and T2D and linear regression analyses were performed to investigate associations between osteoglycin, glycemic markers, bone turnover markers and characteristics. Results: S-osteoglycin did not differ between patients with T1D and T2D (p=0.10). No associations were present between osteoglycin and age, gender, microvascular complications, HbA1c, or plasma glucose in T1D or T2D patients (p>0.05 for all). S-osteoglycin was not associated with levels of bone turnover markers (C-terminal cross-linked telopeptide of type-I collagen (CTX), P-procollagen type 1 amino terminal propeptide (P1NP), P-osteocalcin (OC), P-sclerostin, S-osteoprotegerin (OPG) or S-Receptor Activator of Nuclear factor Kappa beta Ligand (RANKL)) in neither T1D or T2D patients (p>0.05 for all). Conclusion: Osteoglycin levels were similar in T1D and T2D patients. Osteoglycin did not correlate with glucose, HbA1c or any other biochemical marker of bone turnover. Thus, we did not find evidence supporting the existence of an osteoglycin-bone-pancreas axis.